PRINSIP-PRINSIP BUDI PEKERTI HINDU DALAM NYĀYA DARŚANA - I Putu Suweka Oka Sugiharta; I Wayan Yudhasatya Dharma (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
If philosophy is linked to a religious dimension, it will be different from pure philosophy. In Hinduism, religious philosophical views are called darsana. Religious adherents have indeed become more reluctant to express prejudice against religious philosophical views. Because it is believed that these views come from God and are holy. If humans underestimate it, they are threatened with sin. Character actually comes from religious and philosophical views. However, in its development, there has been a tendency for character to be portrayed as practical action. When someone does not show appropriate behavior, they are seen as having low character. However, there is a gap in behavior that is conditioned in such a way as false character. In fact, genuine character is rooted in noble thoughts. If this is understood, then there will no longer be a rigid boundary between thinkers and doers. Because behavior without careful thought is just a pretense. Meanwhile, thoughts without proper behavior are also useless. Complete Hindus, study darsana and apply it to praiseworthy actions. The aim of this research is to examine the philosophical principles of Hindu character in Nyaya Darsana. This research method is qualitative because it is non-numerical. The results of this research are that in Nyaya Darsana, God becomes the highest model of character, the word becomes the religious basis for character, budhi as the ideal basis for character, and pravrtti and karma as the basis for virtuous action. The conclusion of this research is that there are complete moral principles in Nyaya Darsana.